Mutational Heterogeneity in APC and KRAS Arises at the Crypt Level and Leads to Polyclonality in Early Colorectal Tumorigenesis - Gausachs, Mireia; Borras, Ester; Chang, Kyle; Gonzalez, Sara; Azuara, Daniel; Delgado Amador, Axel; Lopez-Doriga, Adriana; San Lucas, F Anthony; Sanjuan, Xavier; Paules, Maria J; Taggart, Melissa W; Davies, Gareth E; et al. (Clinical cancer research, 2017)
The majority of genomic alterations causing intratumoral heterogeneity (ITH) in colorectal cancer are thought to arise during early stages of carcinogenesis as a burst but only after truncal mutations in have expanded a single founder clone. We have investigated if the initial source of ITH is consequent to multiple independent lineages derived from different crypts harboring distinct truncal and driver mutations, thus challenging the prevailing monoclonal monocryptal model. High-depth next-generation sequencing and SNP arrays were performed in whole-lesion extracts of 37 familial adenomatous polyposis colorectal adenomas. Also, ultrasensitive genotyping of hotspot mutations of and was performed using nanofluidic PCRs in matched bulk biopsies ( = 59) and crypts ( = 591) from 18 adenomas and seven carcinomas and adjacent normal tissues. Multiple co-occurring truncal and driver alterations were uncovered in whole-lesion extracts from adenomas and subsequently confirmed to belong to multiple clones. Ultrasensitive genotyping of bulk biopsies and crypts revealed novel undetected mutations that were prominent among carcinomas, whereas abundant wild-type crypts were detected in adenomas. mutational heterogeneity within crypts was evident in both adenomas and carcinomas with a higher degree of concordance between biopsy and crypt genotyping in carcinomas. Nonrandom heterogeneity among crypts was also observed. The striking degree of nonrandom intercrypt heterogeneity in truncal and driver gene mutations observed in adenomas and carcinomas is consistent with a polycryptal model derived from multiple independent initiation linages as the source of early ITH in colorectal carcinogenesis. .